Pengaruh Waktu Tahan Pada Proses Carburizing Terhadap Sifat Mekanik Baja S 45 C Pada Pembuatan Prototype Poros Engkol - Mukro Afrianto; M.Fajar Sidiq; Moh. Agus Sidik (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2020)
This study aims to determine the effect of holding time on the carburizing process of s 45 c steel, especially on the properties of hardness, tensile strength and tensile strength after carburizing with carbon shell charcoal. The research methodology is that the material used is medium carbon steel which is used for the manufacture of the crankshaft. Where the S 45 C steel material is carburizing at a temperature of 9000 C after which a holding time is carried out for 15 minutes, 25 minutes, and 35 minutes then cooled (quenching) quickly through seawater media. Each uses 3 specimens. Furthermore, the process of hardness testing, tensile testing, and bending. The results of this study are the hardness of S 45 C steel in the carburizing process with shell charcoal carbon to a temperature of 900° and holding time for 35 minutes the average hardness is 504 HB, the highest increase is 159.80% from raw material, holding time for 15 minutes and 25 minutes the average hardness was 456 HB and 496 HB increased by 135.05% and 155.67% of the raw material. The magnitude of the tensile strength of S 45 C steel with the carburizing process and holding time for 15 minutes the average tensile strength is 1442.32 N/mm2, the highest increase is 109.74% from the raw material and the carburizing process at a holding time of 25 minutes the average tensile strength is 1392.85 N/mm2, for a holding time of 35 minutes the average tensile strength is 687.29 N/mm2, a decrease of -0.0523% from the raw material. The bending strength of S 45 C steel with carburizing process and holding time of 15 minutes, 25 minutes, and 35 minutes has an average bending strength of 65.85 N/mm2, 56.63 N/mm2, and 62.04 N/mm2 , all experienced a decrease from raw material by 19.97%, 31.18%, 24.60%.